Innovation and small enterprises in the Third World - Dijk, Meine Pieter van.; Sandee, Henry, 1957-; Edward Elgar Publishing (Northampton, Mass. : Edward Elgar Pub., 2002)
Innovation is crucial for small enterprises to become and remain competitive in the global economy. In this book, the authors have combined theoretical insights with comprehensive case studies on innovation among small-scale enterprises in developing countries, paying particular attention to technological change in clusters of small firms.
pt. 1. Framework for understanding innovation diffusion -- pt. 2. Cases of SMES and innovation -- pt. 3. Innovation in times of economic crisis -- pt .4. Mechanisms for innovation diffusion -- pt. 5. Conclusions and recommendations.
Includes bibliographical references and index.
Keywords: Small business -- Developing countries; Small business -- Developing countries -- Case studies; Technological innovations -- Economic aspects -- Developing countries; Technological innovations -- Economic aspects -- Developing countries -- Case studies; Electronic books